Contributions of European research INCLUD-ED for the reduction of early school leaving - Padrós Cuxart, Maria; Duque Sánchez, Elena; Molina Roldán, Silvia (Avances en Supervisión Educativa, 2011)
The challenge of reducing early school leaving in Europe, with special pressure in Spain, leads to the need of evidence based educational policies and measures. This paper presents measures to prevend and reduce early school leaving that have been identified within the research Project INCLUD-ED. Strategies for inclusion and social cohesion in Europe from education. This is the research Project with a higher level and resources developed  since now  in Europe regarding school education. The identified solutions are already being addressed in documents of the European Commission, such as the recent Communication to the European Parliament "Tackiling early school leaving: a key contribution to the Europe 2020 Agenda".
Keywords: early school leaving; successful actions; learning communities